Relationship between Body Image and Adequacy of Iron Intake with Hemoglobin Levels in Adolescent Females - Anisa, Anisa; Ayuningtyas, Rr. Annisa; Jauharany, Firdananda Fikri; Isworo, Joko Teguh (Jurnal Gizi dan Pangan, 2023)
The aim of this study was to analyze the relationship between body image and adequacy of iron intake with blood hemoglobin levels in adolescent females. A total of 26 female students were randomly selected from State High School 2 and State High School 9 Semarang, Indonesia. Data were analyzed using Spearman's rank correlation test. The results showed no association between body image and hemoglobin levels (p=0.795, r=-0.053), or between adequacy of iron intake and hemoglobin levels (p=0.345, r=0.193). Based on the results, there is no relationship between body image and iron intake adequacy with blood hemoglobin levels in female adolescents.